KINERJA PERKERASAN ASPAL BERPORI DENGAN CAMPURAN LIMBAH PLASTIK DAN KARET - Susanto, Hery Awan; Mulyono, Bagyo; Widyaningrum, Arnie; Herry Purnomo, Widhiatmoko (Jurnal Jalan Jembatan, 2023)
One of the measures to mitigate climate change is to to apply a porous asphalt mixture in pavement construction. The use of porous asphalt mixture is still limited, because of low performance compared to some other asphalt mixtures. A comprehensive study to improve the optimal performance necessary to problems improve the application. This research aims to determine the performance of porous asphalt using plastic and used tires waste  mixed into asphalts by using some laboratory testings (both in dry and in wet conditions) according to AAPA 2004. Indirect Tensile Strength (ITS) (both in dry and wet conditions), ravelling, and permeability are obtained with variations plastic and used tires waste levels of 1-3%. There is an increase in Marshall performance, resistance to cracking, ravelling (based on abrasion test) on porous asphalt mixtures with plastic and used tires waste. A porous asphalt mixture with 2% of plastic and used tires waste has produced a good level of durability indicated by the Residual Strength Index (IKS) value and from the Tensile Strength Ratio (TSR) value at all levels of plastic and used tires waste. From the value of porosity and moisture resistance, a decrease in the level of porosity and moisture resistance are shown. The decrease that occurred at 2% plastic and used tires waste level was not too high between dry and wet condition samples. The results of this study recommend that the addition of plastic and used tires waste at 2% can produce a good quality of porous asphalt mixture.